Projection‐transformation method with considering energy conservation. Issue 12 (3rd October 2019) - Yamauchi, Hitoshi; Ozaki, Koichi; Sato, Yoichiro; Fukuta, Tadao; Obunai, Kiyotaka
Abstract: In this paper, a projection‐transformation method that considers the conservation of energy during transformation is proposed. To consider energy conservation, an area‐integration function of the input image is introduced. By conducting the projection‐transformation of this function, energy is conserved during transformation. The pixel value of the transformed image is calculated by integrating the transformed function. The Gauss–Legendre numerical integration scheme is used for the integration calculation. Moreover, the pixel area change during the transformation is considered by using the Jacobian factor. To demonstrate the projection‐transformation, standard images of the SIDBA and SCID datasets are used. Also, the ISO 12233 Test Chart is used for evaluation using high‐frequency images. The quality of the transformed images is evaluated using the structural similarity index and peak signal‐to‐noise ratio values. Because the image quality is affected by the color space, the evaluations are conducted using RGB and YUV color spaces. The results show that the proposed methods produce the highest quality values regardless of the type of image or color space. Moreover, the quality of the transformed image is improved when considering the Jacobian of the pixel area change. The results demonstrate that the proposed method is effective in improving the quality of the projection‐transformed image. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.